2014
DOI: 10.1007/s12975-014-0332-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Clot Aging and Cholesterol Content on Ultrasound-Assisted Thrombolysis

Abstract: Exposure to 2-MHz transcranial diagnostic ultrasound enhances the thrombolytic activity of intravenously administered tissue plasminogen activator (IV-tPA) in acute ischemic stroke (sonothrombolysis). However, rates of arterial recanalization vary widely, depending upon the clot burden, its location, and stroke subtype. We evaluated the influence of age and cholesterol level of the blood clots on sonothrombolysis in an in vitro model. To "age" the clots, serum was replaced by fresh blood periodically. We incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…EPA normally exists in extremely low levels in the brain but can be dramatically elevated after long-term FO supplement [18]. To facilitate the translation of n-3 PUFA treatment for clinical use, future studies should take into consideration the confounding effects from aging and stroke comorbidities [6365], and also test the therapeutic efficacy in models involving tPA thrombolysis [6669]. …”
Section: Discussionmentioning
confidence: 99%
“…EPA normally exists in extremely low levels in the brain but can be dramatically elevated after long-term FO supplement [18]. To facilitate the translation of n-3 PUFA treatment for clinical use, future studies should take into consideration the confounding effects from aging and stroke comorbidities [6365], and also test the therapeutic efficacy in models involving tPA thrombolysis [6669]. …”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the thrombolytic effects of MBs or thrombolytic drugs were varied with different types or ages of thrombi. 1,2 To verify whether the thrombolytic effects of M-MBs would vary with different thrombi, we applied red and white thrombi and two ages of thrombi to research in this study. Since the time window for thrombolytic treatment of acute myocardial infarction is within 12 hours, we used 12-hour clots as older thrombi to investigate the efficacy of sonothrombol-ysis.…”
Section: Preparation and Characterization Of Ex Vivo Macrothrombimentioning
confidence: 99%
“…Recently, our group studied the effects of sonothrom-bolysis in an in-vitro experiment. 12 Blood clots were prepared from horse blood and used to create occlusions in the silicone tubing, mimicking the intracranial arteries, in an in-vitro water tank with controlled temperature. We evaluated the relationship between sonothrombolysis and age of the clot as well as the cholesterol content.…”
Section: In-vitro and Animal Models For Understanding The Mechanism Of Sonothrombolysismentioning
confidence: 99%